An altered nanoemulsion assembly strategy for in-situ synthesis of Co2P/NP-C nanospheres as advanced oxygen reduction electrocatalyst for zinc-air batteries. (15th February 2022) - Shi, Jing; Guo, Xingmei; Liu, Shanjing; Sun, Yue; Zhang, Junhao; Liu, Yuanjun; Zheng, Xiangjun; Kong, Qinghong
Abstract: The design of highly active and stable non-noble metal catalysts for oxygen reduction reaction (ORR) is indispensable for metal-air batteries. Herein, an altered nanoemulsion assembly approach is developed to synthesize fine Co2 P dispersed in N, P doped carbon nanospheres (Co2 P/NP-C) as prominent ORR electrocatalyst for zinc-air batteries (ZABs). A high half-wave potential of 0.81 V vs. RHE and a limiting current density of 4.54 mA cm −2 is exhibited for Co2 P/NP-C, which are comparable with those of commercial Pt/C, indicating excellent ORR electrocatalytic activity. Moreover, a big peak power density of 152.4 mW cm −2 and a high gravimetric energy density of 1286.0 Wh kgZn −1 are delivered for the assembled primary ZAB using Co2 P/NP-C as cathode catalyst with a high open circuit voltage of 1.448 V. The excellent performance should be attributed to the in-situ formed Co2 P nanoparticles and N, P heteroatoms in nanospherical carbon matrix with high accessible surface area, which both provide sufficient catalytic active sites and ensure efficient mass/charge transport in ORR process. Graphical abstract: Image 1 Highlights: An altered nanoemulsion assembly strategy was used to prepare Co2 P/NP-C nanospheres. Co2 P nanocrystallites and N, P heteroatoms were in-situ formed in carbon matrix. High activity and stability for catalyzing oxygen reduction reaction were achieved. The as-assembled zinc-air battery showed high power density and specific capacity.